The Function and Role of the Th17/Treg Cell Balance in Inflammatory Bowel Disease - Jun-bin Yan; Min-min Luo; Zhi-yun Chen; Bei-hui He (Journal of Immunology Research)
Inflammatory bowel disease (IBD) is a chronic, inflammatory, and autoimmune disorder. The pathogenesis of IBD is not yet clear. Studies have shown that the imbalance between T helper 17 (Th17) and regulatory T (Treg) cells, which differentiate from CD4+ T cells, contributes to IBD. Th17 cells promote tissue inflammation, and Treg cells suppress autoimmunity in IBD. Therefore, Th17/Treg cell balance is crucial. Some regulatory factors affecting the production and maintenance of these cells are also important for the proper regulation of the Th17/Treg balance; these factors include T cell receptor (TCR) signaling, costimulatory signals, cytokine signaling, bile acid metabolites, and the intestinal microbiota. This article focuses on our understanding of the function and role of the balance between Th17/Treg cells in IBD and these regulatory factors and their clinical significance in IBD.